PERTAUTAN NILAI AGAMA DALAM TRADISI: PARERESAN DALAM MAKNA KEISLAMAN - Uus Putria (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2022)
The purpose of this study was to determine the local wisdom of the Sundanese people in relation to the natural environment, especially Pareresan in Sangiang, Majalengka Regency. This study is field research, which is a study that examines objects in the field to get data and a clear and concrete picture of things related to the problems studied. The results showed that the existing values were closely related to the Pareresan traditional ceremony. The Pareresan is a tradition to express gratitude for the abundant harvest. The tradition that has been passed down by the ancestors of the Majalengka people of West Java, Indonesia, especially in Sangiang Village has religious values, aesthetic values, mutual cooperation values, the value of deliberation, the value of kindness, the value of gentle Sundanese silih asih, silih asah dan silih asuh. Religious values are the most dominant. The implication of this research is that Pareresan culture needs to be preserved by upholding the Islamic values. Keywords: local wisdom, Pareresan, Sunda, Tradition.